The Peran Person-Organization Fit, Person-Job Fit, dan Kepuasan Kerja Dalam Meningkatkan Kinerja Dosen Universitas Terbuka. - Sylvana, Andi; Awaluddin, Murtiadi; Dueramae, Hussam; Sanusi, Nina Utami Y (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2024)
Lecturers are professionals and scholars whose performance is evaluated based on their success in fulfilling the three pillars of higher education known as Tri Dharma Perguruan Tinggi: education, research, and community service. They bear the responsibility for these tasks, relying on their skills, experience, and dedication within specific time frames. The performance of lecturers significantly influences their academic career progression and the quality of the higher education institution. Several factors can affect lecturers' performance, including person-organization fit, person-job fit, and job satisfaction. This research employs descriptive and verificative analyses. The data were analysed using LISREL Version 8.72 software. This analysis aims to understand the roles of person-organization fit, person-job fit, and job satisfaction in enhancing the performance of lecturers at Universitas Terbuka. The total number of respondents in this study was 223. The conclusions drawn from this research are as follows: Person-Organization Fit has a significant impact on job satisfaction among lecturers at Universitas Terbuka; Person Job Fit significantly affects job satisfaction among lecturers at Universitas Terbuka; Person-Organization Fit significantly influences the performance of lecturers at Universitas Terbuka; Person Job Fit has a significant effect on the performance of lecturers at Universitas Terbuka; Job satisfaction significantly influences the performance of lecturers at Universitas Terbuka; Person-Organization Fit and Person Job Fit jointly have a significant impact on the performance of lecturers at Universitas Terbuka; and Person-Organization Fit, Person Job Fit, and Job Satisfaction together significantly influence the performance of lecturers at Universitas Terbuka.